Traditional Treatment Choices for Managing Dysmenorrhea Among Adolescent Girls: An Application of the Health Belief Model - Khoiriyah, A'maliatul; Demartoto, Argyo; Murti, Bhisma; Novika, Revi Gama Hatta; Febrinasari, Ratih Puspita (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Dysmenorrhea is a common reproductive health problem among adolescent girls and often interferes with daily activities. Various management strategies are used to alleviate dysmenorrhea, including the use of traditional medicine. This study aimed to examine the influence of Health Belief Model (HBM) constructs on the choice of traditional medicine for reducing dysmenorrhea among adolescent girls. Subject and Methods: This quantitative study employed a cross-sectional design carried out in Boyolali Regency, Central Java, Indonesia. A total of 200 female adolescents were selected using stratified random sampling. Data were collected using a standardized questionnaire that had been tested for validity and reliability. Multivariate data analysis was conducted using path analysis to identify both direct and indirect effects among variables. Results: The selection of traditional medicine for dysmenorrhea management among adolescent girls was directly influenced by perceived benefits (b = 1.29; 95% CI= 0.61–1.97; p < 0.001) and perceived severity (b= −0.14; 95% CI= −0.71 to 0.43; p= 0.631). Meanwhile, perceived susceptibility (b= 0.81; 95% CI= 0.17–1.45; p= 0.013), perceived barriers (b= −1.53; 95% CI= −2.29 to −0.77; p < 0.001), cues to action (b= 1.44; 95% CI= 0.80–2.09; p < 0.001), and self-efficacy (b= −0.98; 95% CI= −1.61 to −0.34; p = 0.003) had indirect effects on the choice of traditional medicine. The resulting path model demonstrated good goodness-of-fit. Conclusion: Health Belief Model constructs can be effectively applied as a framework for understanding the selection of traditional medicine. HBM-based interventions that emphasize increasing perceived benefits and managing perceived barriers are recommended to support informed reproductive health decision-making among adolescents